A Conceptual Framework of Cloud-Based Mobile-Retail Application for Textile Cyberpreneurs - Nik Zulkarnaen Khidzir; Wan Safra Diyana Wan Abdul Ghani; Khairul Azhar Mat Daud (IAES Indonesia Section, 2018)
Cloud-based m-retail application is commonly used by internet retailers and cyberpreneurs for conducting online business operations. The emergence of third-party e-commerce platforms along with incentives from Malaysian government has easily enabled the utilization of mobile marketplace app among both Malaysian sellers and customers. As m-retail has just started to gain attention in Malaysia, more works must be done to overcome the academic research limitations in terms of technological and non-technological perspectives. Meanwhile, textile and apparel products are among the most popular to be sold via the internet in addition to the growing number of related businesses. The uses of latest technology such as cloud-based mobile-retail application may help business owners to sustain for business survival. In designing a mobile applications for specific users, a thorough investigation must be performed. A conceptual framework of the apps might be helpful in providing a general overview of required elements for developing a successful mobile-retail applications. Extensive literature reviews, qualitative analysis, interviews and questionnaires have been conducted in designing and validating the proposed framework. The analysis results shows mean values from the survey are > 3.5 for the core element variables in this research. Thus, the statistical analysis validation results indicates the importance of the element as the fundamental component for the proposed framework. Therefore, this paper intends to propose a conceptual framework of cloud-based mobile-retail application specifically to be used by textile cyberpreneurs which might be helpful for related key players.